1980
DOI: 10.1111/j.1748-1716.1980.tb06561.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vagotomy and glucose administration on gastric acid secretion in the Atlantic cod, Gadus morhua

Abstract: Cods were prepared for measurement of gastric acid secretion. Cannulae were implanted for drainage of the stomach and for separate perfusion of the stomach and intestine. Fishes, intestinally perfused with diluted sea-water (33% SW) exhibited high rates of acid secretion. This "basal" secretion was abolished (96% inhibition) by bilateral vagotomy. Perfusion of the stomach with isosmotic glucose (5.5%) diminished the amount of titratable acid in the gastric effluence, and induced oral ingestion of water. Only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This agrees with that the conductance through pores made by the antimicrobial cationic peptide gaegurin 4 was larger in planar bilayers made of PE, PC and PS (80:10:10) compared to membranes composed of only PE and PC (80:20) [63]. A role of sterols with respect to alamethicin channel activity was shown with artificial membranes, i.e ., the presence of cholesterol increased the duration of the alamethicin pore in its open state, indicating a more efficient use of created pores, while the critical concentration of alamethicin needed for pore formation increased [64,65]. Oligomerisation and pore formation by Vibrio cholerae cytolysin also depended on the presence of cholesterol [66].…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with that the conductance through pores made by the antimicrobial cationic peptide gaegurin 4 was larger in planar bilayers made of PE, PC and PS (80:10:10) compared to membranes composed of only PE and PC (80:20) [63]. A role of sterols with respect to alamethicin channel activity was shown with artificial membranes, i.e ., the presence of cholesterol increased the duration of the alamethicin pore in its open state, indicating a more efficient use of created pores, while the critical concentration of alamethicin needed for pore formation increased [64,65]. Oligomerisation and pore formation by Vibrio cholerae cytolysin also depended on the presence of cholesterol [66].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that blockade of gastrin at the parietal cell level is the major mechanism by which VIP inhibits canine gastric acid secretion (Konturek et al 19760). The secretion is dependent on an intact vagal supply (Holstein & Cederberg 1980), but this does not exclude the involvement of a stimulating hormone. The basal plasma concentrations are similar to those measured in the dogfish shark (Humphrey, unpublished) but high when compared to man, dog, and rat (<150 pg/ml with this assay).…”
Section: Discussionmentioning
confidence: 98%
“…The present work also seems to indicate that "basal" acid secretion is depressed by VIP, but the nature of this secretion, though arbitrarily designated "basal", is incompletely characterized. The secretion is dependent on an intact vagal supply (Holstein & Cederberg 1980), but this does not exclude the involvement of a stimulating hormone. Gastrin-IR was in fact detected in codfish plasma but the failure of pentagastrin to stimulate the acid secretion makes it difficult to ascribe part of the "basal" secretion to this immunoreactivity.…”
Section: Discussionmentioning
confidence: 98%
“…Vagotomy has, however, also been reported not to modify the inhibition [9]. In the cod, the vagus is necessary for the basal acid secretion [36], and assuming a potentiating interaction between some component in the basal drive and histamine, inhibition of both basal and histamine(+basal)-stimulated acid secretion could be elicited by the interruption of the vagal drive. The mechanism responsible for the lack of basal secretion during intestinal perfusion with 67% SW is not known but supposing, for the moment, that the vagal drive is depressed, the findings would argue for the involvement of the vagus in the acid inhibitory effect of 5-HT, though not for its pepsigogue effect.…”
Section: Discussionmentioning
confidence: 99%